Implementing STAD Cooperative Learning to Improve Elementary Science Learning Outcomes: A Classroom Action Research - Zahra Zinnira Irwan; Nashrullah Nashrullah; Muslim AR Muslim AR; Arif Firmansyah; Muhammad Nazimuddin Al Kamil; Surahman Wilade (Journal of Innovation and Research in Primary Education, 2026)
Traditional teacher-centered instruction in Indonesian elementary schools limits student engagement and conceptual understanding, particularly in integrated science curricula. This study investigated the effectiveness of Student Teams Achievement Division (STAD) cooperative learning in improving IPAS (Natural and Social Sciences) learning outcomes among fifth-grade students. Employing classroom action research design, this study implemented STAD across two iterative cycles with 32 fifth-grade students at SD Inpres Perumnas Palu during the 2025/2026 academic year. Data were collected through achievement tests, structured classroom observations, and teacher interviews. Quantitative analysis measured individual and classical mastery rates, while qualitative analysis using the Miles and Huberman framework examined engagement patterns and implementation quality. Classical mastery increased substantially from 19% at baseline to 40% in Cycle I and 87% in Cycle II, exceeding the 80% success criterion. Mean achievement scores rose 65% from 49.29 to 81.15. Student engagement improved from 70% to 86%, while teacher implementation quality increased from 75% to 83%. Heterogeneous grouping facilitated effective peer scaffolding, with proportionally greater gains among initially lower-performing students. STAD effectively enhances both academic achievement and student engagement in integrated science instruction. The study demonstrates that structured cooperative learning, supported by reflective practice and iterative refinement, operationalizes constructivist principles and supports holistic student development in resource-constrained educational contexts.